2016
DOI: 10.1007/s00384-016-2630-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fast-track surgery on inflammation and immunity in patients undergoing colorectal surgery

Abstract: The FTS program can decrease inflammation, maintain immune homeostasis, and improve rehabilitation effects in colorectal surgery patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Robust evidence suggested that ERAS played an important role in attenuating the surgical stress response and accelerating the return to baseline in colorectal cancer surgery[ 38 , 39 ], which was afforded eloquent proof in GC surgery. The inflammatory factors, such as CRP, IL-6 and tumor necrosis factor α, are related to the extent of tissue injury caused by surgery[ 40 , 41 ]. In the present study, the ERAS approaches significantly reduced the concentration of CRP and IL-6 in comparison with SC on days 1, 4 and 7 after gastrectomy for GC, which was consistent with accelerated recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Robust evidence suggested that ERAS played an important role in attenuating the surgical stress response and accelerating the return to baseline in colorectal cancer surgery[ 38 , 39 ], which was afforded eloquent proof in GC surgery. The inflammatory factors, such as CRP, IL-6 and tumor necrosis factor α, are related to the extent of tissue injury caused by surgery[ 40 , 41 ]. In the present study, the ERAS approaches significantly reduced the concentration of CRP and IL-6 in comparison with SC on days 1, 4 and 7 after gastrectomy for GC, which was consistent with accelerated recovery.…”
Section: Discussionmentioning
confidence: 99%
“…It have been recognized widely that the advantages of laparoscopic surgery such as alleviating surgical stress and reducing respiratory interference could accelerate postoperative recovery [ 35 37 ]. To date, some authors have reported that ERAS protocol could accelerate recovery by mitigating the inflammatory response [ 14 , 15 , 38 , 39 ]. Our results suggest the combination of the two methods can further alleviate the inflammation and immune inhibition based on the efficacy of a single method.…”
Section: Discussionmentioning
confidence: 99%
“…After reading titles and abstracts, 119 articles that did not meet the inclusion criteria were excluded, leaving 115 articles. After reading the full text and screening according to the inclusion and exclusion criteria and data completeness, a total of 22 articles with 3702 patients were included, including 1906 patients in the ERAS group and 1796 patients in the control group 10–12,15–33 . A flowchart of the article selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…After reading the full text and screening according to the inclusion and exclusion criteria and data completeness, a total of 22 articles with 3702 patients were included, including 1906 patients in the ERAS group and 1796 patients in the control group. [10][11][12][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] A flowchart of the article selection process is shown in Figure 1. The basic characteristics of the included studies are shown in Table 1.…”
Section: Study Selection and Quality Assessmentmentioning
confidence: 99%